Combining Micro and Nanoscale Structures: Emerging Applications of Diatoms - D. Kurkuri, Mahaveer; Saunders, Chris; J. Collins, Patrick; Pavic, Hervoika; Losic, Dusan (Micro and Nanosystems, 2011)
The unique morphologies and properties of the diatom silica shell with its intricate, hierarchically organized three dimensional (3-D) structures with nanoscale dimensions have attracted considerable interest in materials science and nanotechnology in recent years. This review highlights recent emerging applications from diatom nanotechnology research with particular emphasis on applications based on the integration of micro and nanostructures including sensing/ biosensing, drug delivery and chemical-free pest control.
Keywords: Diatoms